Microbial Fuel Cells: Methodology and Technology - Logan, B.E.; Hamelers, B.; Rozendal, R.; Schrder, U.; Keller, J.; Freguia, S.; Aelterman, P.; Aelterman, P.; Rabaey, K.
Microbial fuel cell (MFC)research is a rapidly evolving field that lacks established terminology and methods for the analysis of system performance. This makes it difficult for researchers to compare devices on an equivalent basis. The construction and analysis of MFCs requires knowledge of different scientific and engineering fields, ranging from microbiology and electrochemistry to materials and environmental engineering. DescribingMFCsystems therefore involves an understanding of these different scientific and engineering principles. In this paper, we provide a review of the different materials and methods used to construct MFCs, techniques used to analyze system performance, and recommendations on what information to include in MFC studies and the most useful ways to present results.